O uso dos contos literários no terceiro ano do Ensino Fundamental como contribuição para a formação de leitores competentes - Caetano, Daniela (2022)
This research presents, from the conception of “language”, reading strategies that the teacher can employ in the formation of competent readers, in the third year of elementary school, through literary tales. This achievement stems from the need to investigate the development of reading comprehension and interpretation skills, based on data from the National System for the Evaluation of Basic Education (Saeb), given that these reinforce the reading competence of students. The general objective is to analyze how the use of literary short stories in the third year of elementary school contributes to the development of reading skills in students. The specific objectives are: (1) to find out how teachers work on reading with their students, (2) identify how teachers work with literary tales to develop reading skills and (3) elaborate principles aimed at teaching reading proposals. Regarding the theoretical foundations of the research, those dealing with language and reading, from a socio-interactionist perspective as an instrument of communication and form of interaction, are based mainly on the studies by Cintra and Passarelli (2012), Geraldi (2006) and Passarelli (2004); the concepts related to teaching reading strategies in classroom practice to train competent readers are based on the concepts of Cintra and Passarelli (2012), Jolibert (1994) and Solé (1998); the concepts related to the formation of literature readers, in the understanding of “children's literature” as a fundamental cultural process, in the “tales” genre, are based on the studies of Abramovich (1995), Bettelheim (1980), Carvalho (1985), Coelho (2000; 2012 ) and Zilbermann (1994). In the methodological field, the qualitative approach of Lüdke and André (1986) was used. Data were obtained through questionnaires and semi-structured alterations with three teachers from third-year classes of elementary school who work at a school in the municipal education network in Barueri, in the state of São Paulo. The data analysis stage was organized and grouped into categorization inspired by Passarelli's (2017) ideas – Knowing, Know how to be and Know how – adapted to the theme of this research. Based on the analysis carried out, the teachers believe that, from reading, it is possible to develop reading skills and evidence through daily activities accomplished in the classroom to produce literary tales in the contribution to the formation of competent readers